Generation of optical needles and bright spot arrays through reversing the radiation pattern of collinear antenna array. (7th June 2019) - Yu, Yanzhong; Huang, Han; Lin, Shunda; Chen, Musheng; Zhan, Qiwen
Abstract: An optimization-free approach is proposed for generating optical needle and bright spot arrays with controllable distributions. This is achieved by inversely focusing the radiation pattern from a collinear antenna array whose elements are placed along an optical axis and whose currents in each element also flow along that direction, situated at the focus of a 4pi configuration. The shape and central location of the n th focusing field only depend on the length l n and coordinate z n of the n th element in collinear array, respectively. The number of focal fields is determined by the number of elements in the array.